Development breeding objectives for the nguni cattle breed in South Africa - Matjuda, Lehotlo Ephraim (University of Limpopo (Turfloop Campus), 2012)
Refer to document
Thesis (Ph.D. ( Animal breeding)) --University of Limpopo, 2012
Keywords: Breeding; Nguni cattle; 636.24200968; Animal breeding; Cattle breeding -- South Africa